Analisis Dampak Pengolahan Tanah Terhadap sifat Fisika Dan Kualitas Tanah - Gulo, Arkhipus; Waruwu, Jufriliinus (CV. SINAR HOWUHOWU, 2024)
Proper soil management is very important to maintain land quality and productivity in the long term. This research aims to analyze the impact of soil management on the physical properties and quality of soil. The methods used include collecting soil samples from various fields with different treatments, such as intensive plowing, adding organic fertilizer, and using chemical fertilizers. Laboratory analysis is carried out to measure soil physical parameters, including texture, density, porosity and permeability, as well as aspects of soil quality, such as organic matter, ph and the presence of microorganisms. The research results show that excessive soil management, such as intensive plowing, tends to damage soil structure, reduce porosity, and reduce water absorption capacity. On the other hand, regular use of organic matter can increase soil aggregation, increase water holding capacity, and increase the population of microorganisms that support soil fertility. The conclusion of this research is that sustainable soil management, especially through the addition of organic matter and minimum tillage, has a positive impact on the physical properties and quality of the soil. It is hoped that these results can become a reference in implementing more environmentally friendly and sustainable land management practices.